2007
DOI: 10.1007/s00018-007-7174-z
|View full text |Cite
|
Sign up to set email alerts
|

The CorA family: Structure and function revisited

Abstract: The CorA family is a group of ion transporters that mediate transport of divalent metal ions across biological membranes. Metal ions are essential elements in most cellular processes and hence the concentrations of ions in cells and organelles must be kept at appropriate levels. Impairment of these systems is implied in a number of pathological conditions. CorA proteins are abundant among the prokaryotic organisms but homologues are present in both human and yeast. The activity of CorA proteins has generally b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 53 publications
2
62
2
Order By: Relevance
“…They seem to be one of the hallmarks of the Mg 2þ transporters subgroup A. However, the residues involved in the metal bindings are not conserved in the CorA subgroup B, 21 nor in the ZntB subfamily (Supporting Information Fig. S1).…”
Section: Discussionmentioning
confidence: 99%
“…They seem to be one of the hallmarks of the Mg 2þ transporters subgroup A. However, the residues involved in the metal bindings are not conserved in the CorA subgroup B, 21 nor in the ZntB subfamily (Supporting Information Fig. S1).…”
Section: Discussionmentioning
confidence: 99%
“…As reviewed by Schindl et al, the outer membrane pore forming the Mg 2ϩ entry side comprises the GMN motif and numerous negative electrostatic charges, which might provide ionic selectivity in those transporters possessing the GMN motif (125). As discussed by Niegowski and Eshaghi (98), some of the reported interpretative discrepancies of the three crystallographic studies may be due to deviation in members of the CorA family.…”
Section: Strategy For Identifying Novel Mg 2؉ Transportersmentioning
confidence: 99%
“…I will briefly review plant, bacterial, and yeast transporters as they relate to our newly identified mammalian Mg 2ϩ transporters, because some of these proteins share characteristics with the more ancient forms of transporters. The identification and characterization of plant, prokaryote, and yeast Mg 2ϩ transporters have been extensively reviewed elsewhere (35,70,73,138 transport (30,36,87,93,98,105,168). CorA is the primary Mg 2ϩ uptake transporter in most prokaryotes (140).…”
mentioning
confidence: 99%
“…This transporter has been suggested as being responsible for the major Mg 2+ uptake system in the Bacteria and Archaea. However, it is also believed that, in some family members, it may have a different activity than Mg 2+ transport Rainbow trout, Italy UNIUD020 Niegowski & Eshaghi, 2007). The predicted protein encoded by the sequence SSHI.59 shows homology to the product of the ZP_05668408.1 gene from Enterococcus faecium, a protein from the phosphotransferase system.…”
Section: Resultsmentioning
confidence: 99%